Assessment of workplace bullying: reliability and validity of an Arabic version of the Negative Acts Questionnaire-Revised (NAQ-R). Issue 12 (9th December 2018) - Makarem, Nisrine N; Tavitian-Elmadjian, Lucy R; Brome, Dayana; Hamadeh, Ghassan N; Einarsen, Ståle
Abstract : Introduction: Interest in workplace bullying has been steadily growing since the 1990s, focusing on understanding its driving factors, prevalence rates in different occupations and countries, its consequences, as well as the characteristics of the typical bully and victim. Currently, the Negative Acts Questionnaire-Revised (NAQ-R) is the most frequently used questionnaire to assess workplace bullying. Studies in the Arab world are scarce and to date the NAQ-R has not been validated in Arabic, the official or co-official language in around 25 countries in the Middle East and Asia. The aim of this study was therefore to develop an Arabic version of NAQ-R. Materials and methods: 447 participants aged 18–70 years were recruited through convenient sampling. Exclusion criteria were illiteracy and employment for less than 6 months. Participants were recruited from shops, banks, travel agencies and restaurants in an area in central Beirut around a tertiary care medical centre. A two-stage process was employed to translate the original version of NAQ-R to Arabic. This translated version along with validated Arabic versions of the Satisfaction with Life Scale and the Beck Depression Inventory II were distributed to participants. Results: A 14-item two-factor NAQ-R, with subscales of person-related and work-related bullying, was supported. Reliability coefficients for total and subscale scores of the NAQ-R ranged from 0.63 to 0.90. The Arabic NAQ-R had good concurrent validity as indicated by significant correlations with depression and satisfaction with life ( p < 0.05). Conclusion: NAQ-R was translated to Arabic and adapted. The results revealed acceptable levels of reliability and construct validity. As for the underlying factor structure, it needs to be further supported.